Inferential Procedures in Nonlinear Models: An Application in a UK Industrial Cross Section Study of Factor Substitution and Returns to Scale - Mizon, Grayham E. (Econometrica, 1977)
Grayham E. Mizon, Inferential Procedures in Nonlinear Models: An Application in a UK Industrial Cross Section Study of Factor Substitution and Returns to Scale, Econometrica, Vol. 45, No. 5 (Jul., 1977), pp. 1221-1242